Development of an Educational Package Based on Grandparents’ Lived Experiences in Caring for Their Grandchildren - Mouladoost , Akram; Namdarpour, Fahimeh; Tabrizi , Mehdi (Mental Health and Lifestyle Journal, 2026)
The objective of this study was to develop and content-validate an educational package grounded in the lived experiences of grandparents caring for their grandchildren. This study employed a qualitative, multi-stage design. In the first phase, a descriptive phenomenological approach was used to explore the lived experiences of grandparents involved in caregiving for their grandchildren. Semi-structured, in-depth interviews were conducted with grandparents who met predefined inclusion criteria, and data collection continued until experiential saturation was achieved. Qualitative data were analyzed manually using Colaizzi’s seven-step method to extract meaning units, initial codes, subthemes, and main themes. In the second phase, relevant scientific and professional texts in the fields of aging, caregiving, mental health, and intergenerational relationships were purposefully reviewed to identify educational techniques aligned with the extracted themes. In the final phase, an educational package was designed and its content validity was assessed by a panel of experts in geriatric psychology and related disciplines using content validity ratio and inter-rater agreement procedures. The phenomenological analysis yielded several interrelated main themes, including aging-related psychological vulnerabilities, physical and cognitive changes, social and intergenerational challenges, caregiving tensions, lifestyle disruptions, and dual caregiving outcomes. Negative outcomes encompassed anxiety, depressive affect, irritability, physical strain, social withdrawal, and concerns regarding grandchildren’s emotional security, while positive outcomes included renewed hope, increased self-worth, strengthened family bonds, and enhanced sense of meaning. These findings informed the development of a nine-session educational package addressing emotional regulation, self-care, communication skills, resilience, and meaning-making in caregiving. The findings indicate that grandparental caregiving in later life is a complex experience combining vulnerability and growth, and that an educational package grounded in lived experience can provide a structured, culturally responsive framework to support grandparents’ psychological well-being and caregiving competence.